2015
DOI: 10.1177/1947603515580983
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Dual-Tissue Transplantation for Osteochondral Repair

Abstract: BackgroundNumerous treatment methods for osteochondral repair have been implemented, including auto- and allogeneic osteochondral transplantations, combined bone and chondrocyte transplantations, and synthetic implants, but no gold standard treatment has been established. We present preliminary data on a combined autologous bone and cartilage chips: autologous dual-tissue transplantation (ADTT); an easily applicable, low-cost treatment option for osteochondral repair. The aim of this study was to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
118
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(123 citation statements)
references
References 38 publications
2
118
0
3
Order By: Relevance
“…1 At present many different surgical techniques to repair defective cartilage are on offer for the managing physician. The goal of cartilage repair surgery must be (1) to generate tissue that will finally be as close to the surrounding native tissue as possible (i.e., hyaline cartilage), (2) to reverse clinical symptoms with return to previous activity, and (3) to provide with long-term durability. Tissue quality and clinical symptoms are most likely closely connected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 At present many different surgical techniques to repair defective cartilage are on offer for the managing physician. The goal of cartilage repair surgery must be (1) to generate tissue that will finally be as close to the surrounding native tissue as possible (i.e., hyaline cartilage), (2) to reverse clinical symptoms with return to previous activity, and (3) to provide with long-term durability. Tissue quality and clinical symptoms are most likely closely connected.…”
Section: Discussionmentioning
confidence: 99%
“…Care is taken not to harm the cartilage and foremost the chondrocytes within because these are very susceptible to mechanical force. 7 Fragments are primarily fixed within the defect using a second fibrin glue application that mixes with the fragments and generates a stable fragment and/or fibrin clot as also described by Christensen et al 3 After this step of the procedure, the defect is already filled up to the level of the surrounding cartilage or slightly beneath so the membrane can be placed with ease. Finally and before drying out of the fibrin, the Chondro-Gide membrane is placed on top of the fibrin glue-coated chips (rough side facing the chips) and directly sutured to the surrounding healthy cartilage.…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…20 Furthermore, the process of stem cell procurement, gene transfection, and development of these treatment injections often come with considerably costs, which have yet to be justified for widespread clinical use. 21 However, in Tan et al's evaluation of the cost of tissue engineering, it was found that these methods may actually be associated with lower costs than using material from donors. 22 Despite these limitations, previous evaluations have demonstrated clinical improvements in this cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
“…3D tissue engineering composite biomaterials constructed in vitro can be used to repair, maintain, or improve the damaged tissue by transplanting them into the lesion site . Autologous transplantation is called the “golden standard” of clinical repair treatment, but its small repair area, high secondary incidence of donor area, and insufficient donor sources have been restricting the large‐scale clinical application of autologous transplantation . Tissue engineering not only provides a new therapeutic option to relieve the patient's pain, but more importantly, it overcomes the above difficulties and may be a viable alternative to regenerative therapy close to the gold standard .…”
Section: Introductionmentioning
confidence: 99%